The Unbiased Characteristic of Doppler Frequency in GNSS Antenna Array Processing - Yuchen Xie; Zhengrong Li; Feiqiang Chen; Huaming Chen; Feixue Wang (International Journal of Antennas and Propagation)
The antenna array technology, especially the spaced-time array processing (STAP), is one of the effective methods used in Global Navigation Satellite System (GNSS) receivers to refrain the power of jamming and enhance the performance of receivers in the circumstance of interference. However, biases induced to the receiver because of many reasons, including characteristic of antennas, front-end channel electronics, and space-time filtering, are extremely harmful to the high precise positioning of receivers. Although plenty of works have been done to calibrate the antenna and to mitigate these biases, achieving a good performance of antijamming, high accuracy, and low complexity at the same time still remains challenging. Different from existing works, this paper leverages the characteristic of GNSS signal’s Doppler frequency in STAP, which is proven to remain unbiased to solve the problem, even when the nonideal antennas are used and the interference circumstance changes. Since the integration of frequency is carrier phase, the unbiased Doppler frequency leads to an accurate estimation of carrier phase which can be used to calibrate the antenna array without extra apparatus or complicating algorithms. Therefore, a simple Doppler-aid strategy may be developed in the future to solve the difficulty of STAP bias mitigation.